THE POETRY OF CHRISTOPHER OKIGBO: NEW PERSPECTIVES AND CURRENT TRENDS - Ukah, Gabriel Oche; Iwuoha, Emmanuel A. (EBSU Journal of Social Sciences and Humanities, 2022)
Christopher Okigbo was a promising poet as at the time his life was cut short during the Nigeria-Biafra Civil War that began in the year 1967. Towards the end of his life, his poetry began tilting towards the themes of homecoming, return to one’s roots and a style now known to be literary symbiosis—a mixture of the traditional literature and the written medium. This is done by sourcing one’s literary material from Africa’s rich cultural residue. In this study, we are concerned about the relevance of Okigbo’s poetry to contemporary Nigeria, and by extension, Africa. We discussed his poems which feature the themes highlighted such as homecoming to one’s roots and focus on other afro-centric issues. From our analysis, it is clear that his poems remain relevant today as much as they were years back. We also realize that the issues of homecoming and the return to one’s roots he highlighted in his poems are current issues that Africans still have to continue to focus on. The tide of westernization has been growing on abated and an equal dose of a renewed campaign to return to one’s root has to follow. Literary symbiosis remains relevant because the traditional literature enriches the written one while the written medium helps to preserve the traditional literature which exists orally.